STUDI DESKRIPTIF HASIL BELAJAR MAHASISWA PADA MATA KULIAH CHASSIS OTOMOTIF - Siti Nur Aisyah, - (2020)
This research aims to describe the description of learning incourses chassis automotive and to describe student learning outcomes incourses chassis automotive through online learning using interactive media in collaboration with AhaSlides and Zoom during the COVID-19 pandemic. Learning description is explained starting from the process of planning, implementing, and evaluating learning. The results of the study were carried out to determine the extent of students' understanding of the steering system material in the subject chassis automotive after carrying out learning using AhaSlides and Zoom. This research method using quantitative descriptive method. The sample selected in this study were students of the Department of Mechanical Engineering, Automotive Concentration in semester 7. Answers to the description of learning in subject chassis automotive used a questionnaire instrument, while to determine student learning outcomes using a test instrument. The results of this study found that the majority of the learning planning aspects were in the medium category, the implementation aspects of learning were in the high category, and the evaluation process aspects were in the high category. Student learning outcomes after implementing online learning obtained an average of 2.8 and 12 students passed this course.